2021
DOI: 10.1038/s41419-021-03634-7
|View full text |Cite
|
Sign up to set email alerts
|

ADGRA1 negatively regulates energy expenditure and thermogenesis through both sympathetic nervous system and hypothalamus–pituitary–thyroid axis in male mice

Abstract: Adhesion G protein-coupled receptor A1 (ADGRA1, also known as GPR123) belongs to the G protein-coupled receptors (GPCRs) family and is well conserved in the vertebrate lineage. However, the structure of ADGRA1 is unique and its physiological function remains unknown. Previous studies have shown that Adgra1 is predominantly expressed in the central nervous system (CNS), indicating its important role in the transduction of neural signals. The aim of this study is to investigate the central function of Adgra1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…TH is the rate-limiting enzyme in the synthesis of norepinephrine, a sympathetic neurotransmitter. 54 Increased expression of TH indicates activation of local sympathetic nerve fibers, 13 , 54 and increased expression of UCP1 indicates activation of BAT or beige fat. 23 Previous research found some interesting interactions between sympathetic nerves and adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…TH is the rate-limiting enzyme in the synthesis of norepinephrine, a sympathetic neurotransmitter. 54 Increased expression of TH indicates activation of local sympathetic nerve fibers, 13 , 54 and increased expression of UCP1 indicates activation of BAT or beige fat. 23 Previous research found some interesting interactions between sympathetic nerves and adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine hydroxylase is the rate-limiting enzyme in the synthesis of norepinephrine, a sympathetic neurotransmitter. 48 Increased expression of tyrosine hydroxylase indicates activation of local sympathetic nerve fibres. 40 , 48 Increased expression of UCP1 indicates white fat browning or activation of brown/beige-like adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Increased expression of tyrosine hydroxylase indicates activation of local sympathetic nerve fibres. 40 , 48 Increased expression of UCP1 indicates white fat browning or activation of brown/beige-like adipose tissue. 17 We also detected tyrosine hydroxylase and UCP1 expression in other beige/brown fat depots by immunofluorescence to confirm this HIIT effect.…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 is known for its role in mediating anorexic responses, and its presence in EVs suggests a pathway by which tumors can systemically affect appetite and energy balance. Additionally, EVs can influence the sympathetic nervous system’s activity [ 128 ], leading to increased energy expenditure [ 129 ] and contributing to muscle wasting [ 130 ]. This interaction further exemplifies the complex ways in which EVs can modulate systemic metabolic responses in cancer cachexia.…”
Section: Evs and Pathogenesis Of CCmentioning
confidence: 99%